A NARRATIVE INQUIRY OF STUDENT TEACHERS MULTIMODAL PRACTICE EXPERIENCES IN THE INDONESIAN ESP CLASSROOM CONTEXT - Elih Sutisna Yanto; Hikmah Pravitasari (Universitas Wiralodra, 2020)
Drawing on narrative inquiry aiming to understand the experience of student teachers learning context texts through different modes of meaning. This paper reports on the use of narrative frames as a mean of investigating the intersemiotic practice experiences of student teachers majoring in English education program in Karawang, West Java, Indonesia. Students in depth interview data revealed that multimodal practice has the potential to promote the role of student teachers as designers and navigators in reading English disciplinary texts. In addition, multimodal reading encourages the student teachers to become autonomous language learners. Moreover, multimodality reading tasks can scaffold students in comprehending academic language and in increasing students’ academic vocabulary development as well. These findings have implications for policy makers and teacher educators.